2002
DOI: 10.1124/jpet.102.038034
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Actions of a Novel, Potent, Tissue-Selective Benzopyran Estrogen

Abstract: We have identified a new benzopyran derivative, 3-(4-methoxy) phenyl-4- [[4-[2-(1-piperidinyl)ethoxy]phenyl]methyl]-2H-1-benzopyran-7-ol hydrochloride (CHF 4227), with improved in vivo estrogen agonist/antagonist effects. CHF 4227 binds with high affinity to the human estrogen receptor-␣ and -␤ (dissociation constant K i ϭ 0.017 and 0.099 nM, respectively). In immature rats, oral administration of CHF 4227 for 3 days inhibited the uterotrophic action of 17␣-ethynyl estradiol (EE2) (ED 50 ϭ 0.016 mg/kg ⅐ day); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…(4). Compared with raloxifene, CHF4227 binds to ERα and ERβ with higher affinity and inhibits the uterotropic action of 17alpha-ethynyl estradiol with more potency [184]. CHF4227 significantly prevents the development of DMBA-induced mammary tumors in rats [184].…”
Section: New Sermsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4). Compared with raloxifene, CHF4227 binds to ERα and ERβ with higher affinity and inhibits the uterotropic action of 17alpha-ethynyl estradiol with more potency [184]. CHF4227 significantly prevents the development of DMBA-induced mammary tumors in rats [184].…”
Section: New Sermsmentioning
confidence: 99%
“…Compared with raloxifene, CHF4227 binds to ERα and ERβ with higher affinity and inhibits the uterotropic action of 17alpha-ethynyl estradiol with more potency [184]. CHF4227 significantly prevents the development of DMBA-induced mammary tumors in rats [184]. It preserves bone mass without affecting uterine weight and decreases serum cholesterol and fat mass in ovariectomized rats [185].…”
Section: New Sermsmentioning
confidence: 99%
“…CHF 4227.01 is a new benzopyran derivative recently characterized as a SERM with a promising estrogen agonist/antagonist profile on bone, serum lipids, uterus, and breast (13) . In these initial pharmacologic studies, CHF 4227.01 was more potent than RLX on bone and serum lipid endpoints, and it prevented the development of chemically induced breast tumors in the rat (13) .…”
Section: Discussionmentioning
confidence: 99%
“…This was a dose‐finding, placebo‐controlled study with three active comparators. CHF 4227.01 was identified in a screening for tissue‐selective estrogenic compounds, and it was found to have a superior estrogen agonist/antagonist activity relative to RLX in bone, serum lipids, and uterine tissue (13) . CHF 4227.01, RLX, and LFX were synthesized by Chiesi Framaceutici (Parma, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Galbiati et al [37] have identified a new benzopyran derivative, CHF 4227 (Fig. 4), with high affinity to the human ER and ER with dissociation constant of 0.017 nM and 0.099 nM, respectively.…”
Section: Benzopyranmentioning
confidence: 98%